Reimagining circularity : Actions for optimising the use of existing buildings - Lundgren, Rebecka; Kyrö, Riikka; Toivonen, Saija; Tähtinen, Lassi (Buildings & Cities, 2025)
Transitioning towards a circular economy, where the existing building stock is more efficiently used, would significantly reduce material and energy use, emissions, and waste from the built environment sector. This study focuses on exploring what conditions are needed for circularity by imagining preferable circular futures for a 2035 timeframe and understanding the required actions to achieve them. Futures studies methods are used to focus on preferable futures and backcasting. A series of seven backcasting workshops with experts identified actions which were subsequently analysed using thematic analysis. A rapid evidence assessment was then employed to evaluate whether these actions were currently practiced or novel approaches. Two main themes were elicited based on the expected agency: ‘policymakers’ (regulations, incentives, etc.), and ‘organisations’ (industry and firm levels). Findings suggest that many of the suggested actions within these themes already exist; however, they require reinforcement. Novel but incremental actions hold potential for implementation and align with existing initiatives. Novel radical actions present an opportunity for a paradigm shift, although both external disruption and internal renewal are likely to be required. Several identified actions present opportunities to overcome the barriers found in previous research.